Estrategias metodológicas para la interpretación y el análisis de la obra literaria El Ingenioso Hidalgo Don Quijote de la Mancha - Marlene Aguirre-Chaves; Silvia Elena García-Vargas (Universidad Nacional, Costa Rica, 2006)
This methodological proposal came up from an investigative study that was done with high school teachers in the subject of Spanish with the objective of knowing the methodological strategies that are used in the classroom space to comprehend and analize the literary work of El Ingenioso Hidalgo Don Quijote de la Mancha. The objectives that were established were the following: To identify the techniques and instruments that the Spanish teachers developed to study the literary work of El Ingenioso Hidalgo Don Quijote de la Mancha. • To know the methodology that is used by Spanish teachers to developed the literary work of El Ingenioso Hidalgo Don Quijote de la Mancha. • To propose a didactic unit to develop the multiple intelligencies in the literary study of the literary work of El Ingenioso Hidalgo Don Quijote de la Mancha. After analyzing the data, a series of methodological strategies to interpret and analyse the novel El Ingenioso Hidalgo Don Quijote de la Mancha, wich contributes to improve the teaching and learning process in the Spanish subject, in particular, to change the negative perception that the students have about reading the masterpiece of Miguel de Cervantes.